Capabilities for Strategic Adaptation: Micro-Foundations, Organizational Conditions, and Performance Implications - Andreas Philipp Distel (Copenhagen Business School (CBS), 2016)
This dissertation explores capabilities that enable firms to strategically adapt to environmental changes and preserve competitiveness over time – often referred to as dynamic capabilities. While dynamic capabilities being a popular research domain, too little is known about what these capabilities are in terms of their constituent elements, where these capabilities come from, and how their effectiveness can be fostered. Thus, the dissertation's aim is to address these gaps by advancing our understanding of the multilevel aspects and micro-foundations of dynamic capabilities. In doing so, it focuses on capabilities for sensing and seizing new business opportunities and reconfiguring corporate resources. More specifically, the dissertation examines the role of key organization members, such as knowledge workers and top managers, in defining and building these capabilities. Moreover, it investigates how organizational conditions, such as organizational design, support the emergence and performance of such capabilities. In detail, the dissertation consists of three self-contained research papers. The first paper is a systematic, multilevel review of the innovation literature; it reinterprets evidence from prior empirical studies through the dynamic capabilities lens and develops propositions for future research. The second paper is an empirical study on the origins of firm-level absorptive capacity; it explores how organization-level antecedents, through their impact on individual-level antecedents, influence firms' ability to absorb and leverage new knowledge. The third paper is an empirical study which conceptualizes top managers' resource cognition as a managerial capability underlying firms' resource adaptation; it empirically examines the performance implications of this capability and organizational contingencies affecting the capabilityperformance link. Taken together, the dissertation develops new insights into the nature, origins, and management of dynamic capabilities and opens up the black box of what enables firms to strategically adapt.
hdl:10398/9370
Keywords: 650